(untitled) (Revista de Ciências Agroveterinárias, 2015)
Dois Vizinhos municipality, as well as much of the Southwest Paraná, Brazil, show favorable environmental conditions for the commercial cultivation of fig trees. However, due to lack of tradition cultivation of fruit trees, including fig trees, in the region, there is insufficient data regarding the optimal number of branches order to maintain the commercial production of figs. The objective was to evaluate the intensity of thinning of branches in ‘Roxo de Valinhos’ figs related to the branches growth, health and yield of plants, and fruit quality. The experiment was carried out in a randomized block design with four replications and two plants in each experimental unit, from August 15, 2011, up to April 20, 2012, in Dois Vizinhos, PR, Brazil. The treatments were: check, 12, 18, 24, 30, 36, 42, and 48 branches. The thinning of branches reduced production; however it does not affect the physicochemical quality of fruits. The branches growth and severity of leaf rust were not affected by thinning of branches.